Fibrinogen involvement in hemorheology and inflammation - Saldanha, Carlota (2019)
The aim of this chapter is to review the knowledge obtained from; (i) ex vivo and in vitro studies about the effects of human soluble fibrinogen molecules on blood components behavior and their effects on physiological and pathophysiological conditions, and (ii) in vitro studies conducted on experimental animal models. Ex vivo studies which demonstrated the hemorheogical participation of plasma fibrinogen and its involvement in inflammatory vascular disease will be described. In vitro studies of fibrinogen binding to erythrocyte and neutrophils targets and their influence (at normal and high concentrations) on the biorheology properties of erythrocyte (NO metabolism under the external presence of endogenous or exogenous body molecules and by intra erythrocyte manipulation of redox or protein phosphorylation status) and on neutrophils activation will be presented. In vivo studies on the presence and absence of soluble fibrinogen in the bloodstream, and to enable the leukocyte recruitment will be presented. The participation of erythrocyte in leukocyte recruitment in inflammation will also be described.